Unsymmetrical nonplanar 'push–pull' β-octasubstituted porphyrins: facile synthesis, structural, photophysical and electrochemical redox properties. Issue 40 (26th September 2019) - Rathi, Pinki; Butcher, Ray; Sankar, Muniappan
Abstract : β-Octasubstituted porphyrins having three different substituents (Ph, Br and NO2 ) have been synthesized. They exhibited highly red-shifted absorption spectral features with tunable redox properties leading to a very low HOMO–LUMO gap as compared to MTPPs. Abstract : Mixed substitution at the β-position of porphyrins influences their photophysical and electrochemical redox properties. Two new series of asymmetrically mixed β-octasubstituted porphyrins viz . MTPP(Ph)2 Br5 X (X = NO2 or Br and M = 2H, Co(ii ), Ni(ii ), Cu(ii ), and Zn(ii )) have been synthesized and characterized by various spectroscopic techniques. The single crystal X-ray structure of H2 TPP(NO2 )(Ph)2 Br5 showed a nonplanar saddle shape conformation of the macrocyclic core. Furthermore, the fully optimized geometries confirmed the saddle shape conformation of H2 TPP(Ph)2 Br5 X (X = NO2 or Br). Electronic spectra revealed a significant bathochromic shift by appending both electron donor and acceptor substituents at the β-position of the meso -tetraphenylporphyrin skeleton, which reflects the following order H2 TPP < H2 TPP(NO2 ) < H2 TPP(NO2 )(Ph)2 < H2 TPP(Ph)2 Br6 < H2 TPP(NO2 )(Ph)2 Br5 . H2 TPP(Ph)2 Br5 X (X = NO2 or Br) exhibited a significant bathochromic shift (Δ λ max = 53–61 nm) in the Soret band and (Δ λ max = 90–95 nm) in the longest wavelength Q x (0, 0) band as compared to H2 TPP. Nonplanar conformations and electron withdrawing β-substituents induce higher protonation and deprotonation constants for H2 TPP(NO2 )(Ph)2 Br5 and H2 TPP(Ph)2 Br6 as compared to precursor porphyrins viz . H2 TPP, H2 TPP(NO2 ) and H2 TPP(NO2 )(Ph)2 . The electronic spectral properties and redox potentials of MTPP(Ph)2 Br5 X (X = NO2 or Br and M = 2H, Co, Ni, Cu and Zn) are affected by β-substituents at the periphery of the porphyrin core. Redox tunability was achieved by appending push–pull substituents at the β-position of the MTPP (M = 2H, Co II, Ni II, Cu II, and Zn II ) skeleton of the macrocycle. CuTPP(Ph)2 Br6 and CuTPP(NO2 )(Ph)2 Br5 exhibited a dramatically reduced HOMO–LUMO gap with a difference of 0.55 V and 0.62 V, respectively as compared to CuTPP due to the push–pull effect of β-substituents and nonplanarity of the porphyrin core.